Interculturality between Mexico and Japan: New Virtual Exchange Practices - Diez Irizar, Gisela A.; Reyes Cruz, Sofia B. (Revista Lengua y Cultura, 2025)
This article presents the interests and thematic focuses of two universities with an orientation towards internationalization: Universidad Autónoma del Carmen in Campeche, Mexico, and Ritsumeikan University in Osaka, Japan. Using a quantitative approach and a positivist paradigm, the study followed an experimental research design, characterized by three fundamental aspects: control, manipulation, and observation. The aim was to develop intercultural competence in both Japanese and Mexican students through online interactions. Initially, communication took place in a private Facebook group, followed by Zoom meetings, to support the students in becoming well-prepared future professionals. The student exchange was guided by the instructor, with groups formed based on the Spanish language proficiency of the Japanese students, according to the Common European Framework of Reference for Languages. The Japanese students were learning Spanish as their second foreign language, while Mexican students were studying English. The topics discussed in the Facebook group were centered around common cultural interests, while the Zoom sessions lasted 60 minutes each, incorporating the Tandem collaborative learning model. The Beliefs, Events and Values Inventory (BEVI) questionnaire was administered at the beginning and end of the sessions to measure changes in intercultural competence. At the conclusion of the project, a satisfaction survey was conducted, yielding highly positive results. Both cultural groups showed increased empathy, understanding, and respect for each other’s culture, among other values.